2021
DOI: 10.3390/microorganisms9040820
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Norepinephrine on Mono-Species and Dual-Species Staphylococcal Biofilms

Abstract: The effect of norepinephrine (“NE”) on Gram-negative bacteria is well characterized; however, little is known about the impact of NE on cutaneous Gram-positive skin residents, especially staphylococci. In this study, the impact of NE on monospecies and dual-species biofilms of Staphylococcus epidermidis and S. aureus model strains was investigated for the first time. Biofilms were grown in two different models (on polytetrafluoroethylene (“PTFE”) cubes and glass microfiber filters (“GMFFs”)) and additionally k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The brain modulates gut function through the hypothalamic-pituitary-adrenal axis and the autonomic nervous system; norepinephrine, for example, is released by the brain during stress and has been found to stimulate gut pathogen proliferation. 3 Conversely, the gut modulates CNS functions through involving a variety of microbiota-derived metabolites and products, neuroactive substances, and gut hormones that traverse through the enteric nervous system, vagus nerve, circulatory system, or immune system to reach the brain ( Figure 1 ). 4 Collectively, these pathways are referred to as the microbiota-gut-brain axis (MGBA).…”
Section: The Microbiota-gut-brain Axismentioning
confidence: 99%
“…The brain modulates gut function through the hypothalamic-pituitary-adrenal axis and the autonomic nervous system; norepinephrine, for example, is released by the brain during stress and has been found to stimulate gut pathogen proliferation. 3 Conversely, the gut modulates CNS functions through involving a variety of microbiota-derived metabolites and products, neuroactive substances, and gut hormones that traverse through the enteric nervous system, vagus nerve, circulatory system, or immune system to reach the brain ( Figure 1 ). 4 Collectively, these pathways are referred to as the microbiota-gut-brain axis (MGBA).…”
Section: The Microbiota-gut-brain Axismentioning
confidence: 99%
“…The gut modulates several functions in the brain by bacteria-derived metabolites, hormones, and neuroactive substances reaching the CNS via the vagus nerve, enteric nervous- and circulatory system, and immune system (Long-Smith et al, 2020 ). Conversely, the central nervous system modulates gut function through the hypothalamic-pituitary-adrenal axis, as well as the autonomic nervous system (Mart'yanov et al, 2021 ). The composition and activity of microbiota in the GI tract is highly dynamic and influenced by internal factors, such as age and genetics of the host, as well as external factors including dietary changes, and over-use of antibiotics (David et al, 2014 ; de la Cuesta-Zuluaga et al, 2019 ; Vich Vila et al, 2020 ).…”
Section: Gut-brain-axis In Agingmentioning
confidence: 99%
“…Iron sequestration is mainly due to the mammalian ferric-iron-binding proteins transferrin in serum and lactoferrin in mucosal secretions (Mietzner and Morse, 1994). A strategy that bacteria often employ to collect essential iron is the production and utilization of siderophores, that possess high affinity for ferric iron Freestone et al, 1999, Freestone, 2013Coulanges et al, 1997Coulanges et al, 1998Belay and Sonnenfeld, 2002Mart'yanov et al, 2021Lyte et al, 2003Roberts et al, 2002(Ratledge and Dover, 2000. The catechol core found in many siderophores is also present in the stress-related hormones of the catecholamine family.…”
Section: Modulation Of Bacterial Physiology Effect On Growth and Capture Of Ironmentioning
confidence: 99%
“…The impact of catecholamines on mixed biofilms remains to be investigated in the future, to better understand the competition between bacteria in ecological niches. A recent publication explored for the first time the impact of NE on monospecies and dual-species biofilms of S. epidermidis and S. aureus (Mart'yanov et al, 2021). These authors showed that NE can affect the biofilm formation of both species with a strong dependence on aerobic or anaerobic culture conditions.…”
Section: Effect On Biofilmmentioning
confidence: 99%